2014 IEEE International Conference on Services Computing 2014
DOI: 10.1109/scc.2014.21
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Web Service Sub-chain Ranking and Recommendation

Abstract: Nowadays, an increasing number of geospatial Web services (GWSs) are built and being available on the Web for the accessibility and processing of geospatial information. Given the requirement specified by certain users, normally a composition of GWSs, rather than a single GWS, can fulfill this requirement. Consequently, retrieving and recommending sub-chains of possible service invocations is an important research challenge. Leveraging the semantic similarity between the name and text description of parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Zhou et al introduced an approach to identifying and recommending scientific workflows for reuse and repurposing with a layer hierarchy, which adopted a graph skeleton-based clustering technique to cluster the core workflows [26]. In [27], the researcher also retrieved and recommended subchains of possible service invocations by leveraging the semantic similarity between the name and textual description of parameters, where a network model was constructed to represent possible invocations between operations; the results proved that the researcher's approach could solve the problem of a geospatial Web service. An automated filtering mechanism capable of categorizing members within a group based on their response patterns was proposed in [28] by Thampi; the mechanism clustered user posts into groups based on stylistic, thematic, and emotional aspects.…”
Section: Location-based Recommendationmentioning
confidence: 99%
“…Zhou et al introduced an approach to identifying and recommending scientific workflows for reuse and repurposing with a layer hierarchy, which adopted a graph skeleton-based clustering technique to cluster the core workflows [26]. In [27], the researcher also retrieved and recommended subchains of possible service invocations by leveraging the semantic similarity between the name and textual description of parameters, where a network model was constructed to represent possible invocations between operations; the results proved that the researcher's approach could solve the problem of a geospatial Web service. An automated filtering mechanism capable of categorizing members within a group based on their response patterns was proposed in [28] by Thampi; the mechanism clustered user posts into groups based on stylistic, thematic, and emotional aspects.…”
Section: Location-based Recommendationmentioning
confidence: 99%
“…The preliminary result of this research has been reported in our previous work (X. Wang, Cheng et al, 2014). This paper gives a more comprehensive presentation and discussion about sub-chain retrieving, ranking, and recommendation techniques we have developed, including the details of definitions, tractable algorithms, and evaluation of algorithms.…”
Section: Introductionmentioning
confidence: 99%